2019
DOI: 10.3389/fpls.2019.00771
|View full text |Cite
|
Sign up to set email alerts
|

Reduced 15N Losses by Winter and Spring Night-Warming Are Related to Root Distribution of Winter Wheat

Abstract: To develop efficient N management strategies for high wheat NUE and minimizing the environmental impact of N losses under asymmetric warming, 15 N micro-plot experiments were conducted to investigate the effects of night-warming during winter (warming by 1.47–1.56°C from tillering to jointing), spring (warming by 1.68–1.82°C from jointing to booting), and winter + spring (warming by 1.53–1.64°C from tillering to booting) on root growth and distribution of winter wheat, the fates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
2
1
0
Order By: Relevance
“…From our results of 15 N labelled urea amendment experiment, the percentage of total nitrogen from 15 N urea was more than 10% higher under N-LT than that under LT-N, indicating that nitrogen applied prior to low temperature better mitigated the injury of wheat roots caused by low-temperature stress (Table 3). Our finding was in agreement with the reports by Azam et al [37] and Hu et al [38], who reported that better roots were conducive to the absorption and utilization of soil nitrogen and fertilizer. These results further confirmed our hypothesis from the perspective of nitrogen uptake and utilization that nitrogen application prior to low-temperature stress was more beneficial to recover wheat growth, as compared with the nitrogen post low-temperature stress.…”
Section: Changes In Nitrogen Uptake and Utilization With Remedial Fer...supporting
confidence: 94%
“…From our results of 15 N labelled urea amendment experiment, the percentage of total nitrogen from 15 N urea was more than 10% higher under N-LT than that under LT-N, indicating that nitrogen applied prior to low temperature better mitigated the injury of wheat roots caused by low-temperature stress (Table 3). Our finding was in agreement with the reports by Azam et al [37] and Hu et al [38], who reported that better roots were conducive to the absorption and utilization of soil nitrogen and fertilizer. These results further confirmed our hypothesis from the perspective of nitrogen uptake and utilization that nitrogen application prior to low-temperature stress was more beneficial to recover wheat growth, as compared with the nitrogen post low-temperature stress.…”
Section: Changes In Nitrogen Uptake and Utilization With Remedial Fer...supporting
confidence: 94%
“…In our study, the residual fertilizer 15 N remained mainly in the top 20 cm soil though frequent rainfall occurred during the soybean and maize growing seasons. It might be attributed to the microbial immobilization and some adsorption of mineral N forms (presumably NH + 4 ) in exchangeable sites of the topsoil, in line with other studies (Liu et al, 2015;Karwat et al, 2017;Hu et al, 2019;). Inversely, higher fertilizer 15 N accumulated in the 20-40 cm soil layer in North Central China, indicating that more N leaching occurred than in our study (Quan et al, 2020).…”
Section: N Recovery Efficiency In the Soybean Seasonsupporting
confidence: 88%
“…The percentage of 15 N-urea taken up by soybean or maize (Ndff) was calculated as ( Hu et al., 2019 ):…”
Section: Methodsmentioning
confidence: 99%